Analisis Kepuasan Konsumen Berbasis Metode Importance Performance Analysis (IPA) pada Kafe Kopi XYZ - Arif Luqman Ibrahim; Evi Tri Anjani; Putri Agustina; Siti Syarah Fatiqiyah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Customer satisfaction is a key factor in business success and sustainability, especially in the competitive café industry such as in Bogor. Xyz Coffee Cafe, with its unique nature concept and guaranteed coffee product quality, strives to understand and meet consumer expectations in order to maintain its position in the market.The aim of this study is to analyse consumer satisfaction at Xyz Coffee Cafe using the Importance-Performance Analysis (IPA) method.This study uses a qualitative descriptive approach with quantitative analysis. Data was collected through questionnaires to 54 respondents who had visited Xyz B Coffee Cafe. The results of the analysis show that the cafe has a good performance in maintaining consumer interests in most attributes, with strategic recommendations to improve certain aspects to maintain and increase customer satisfaction.